2014
DOI: 10.1177/1538574413518120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Readmission Rates for Carotid Endarterectomy Versus Carotid Artery Stenting in the US Medicare Population

Abstract: Interventions for carotid artery disease had high overall readmission rates. After adjustment for comorbidities, utilization of less invasive techniques (CAS) did not result in lower readmission rates. Further evaluation is needed to determine strategies to reduce hospital readmission rates after carotid interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
5
21
1
Order By: Relevance
“…Consistent with prior investigators, we found that CAS patients were more likely to be readmitted than CEA patients (2). The difference in the risk of readmission is likely driven in part by patient selection.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with prior investigators, we found that CAS patients were more likely to be readmitted than CEA patients (2). The difference in the risk of readmission is likely driven in part by patient selection.…”
Section: Discussionsupporting
confidence: 91%
“…Among Medicare patients undergoing carotid revascularization, 9.6% were readmitted within 30 days of discharge (2,69). A high proportion of readmissions occurred within the first 7 days of hospital discharge, and readmissions were associated with a wide range of principal diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations